The Influence of Financial Literacy on Financial Behavior and Financial Management of MSME Actors In Pasar Village, Gunungsitoli District - Lombu, Vivin Putri Hartaty; Hulu, Perlindungan Faebuadodo; Kakisina, Sophia Molinda; Gulo, Heniwati (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze the influence of financial literacy on financial behavior and financial management in Micro, Small, and Medium Enterprises (MSMEs) in Pasar Village, Gunungsitoli District. The background of the study indicates that MSMEs have a crucial role in the Indonesian economy, but many MSMEs still face challenges in financial management due to a lack of financial literacy. This study used a quantitative approach by distributing questionnaires to 158 MSMEs in the area. The results of the analysis indicate that financial literacy has a positive and significant influence on both financial behavior and financial management of MSMEs. MSMEs with higher levels of financial literacy tend to exhibit healthier financial behaviors, such as the ability to manage expenses, create budgets, and save. Similarly, good financial literacy significantly improves MSMEs' abilities in planning, recording, reporting, and evaluating business finances. Multivariate analysis confirmed that financial literacy simultaneously significantly influences both aspects. The high coefficient of determination (80.7% for financial behavior and 83.7% for financial management) indicates that financial literacy is a dominant factor in explaining variation in both dependent variables.